2022
DOI: 10.1177/1069031x221123265
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Royalty Rates in International Franchising?

Abstract: Royalty rates are an essential contractual provision to reduce the risk of opportunism in franchising partnerships, many of which are international. However, extant research provides limited insights into the factors that determine the level of royalty rates in international franchise agreements. To address this gap, the authors conceptualize and empirically test a model that treats country characteristics (economic potential, legal rights protection, and cultural distance) and contract characteristics (territ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
1
1
0
Order By: Relevance
“…Prior researchers have investigated the factors that influence franchise fees mostly based on agency problems and have suggested that the fee structure is determined to minimize agency problems between franchisors and franchisees and induce the best efforts of each party during the contract period (e.g., Brickley 2002;Lafontaine and Shaw 1999;Maruyama and Yamashita 2012;Mathewson and Winter 1985;Roh 2000;Vázquez 2005). Specifically, Zeißler et al (2023) provided empirical evidence that factors to reduce the risk of opportunism (i.e., economic potential, legal right protection, and contract duration) are important for franchise fee decisions in the international franchise setting as well as in the national context, which confirms recent findings on the agency problems (Jayachandran et al 2013;Lanchimba et al 2018). These studies helped us learn the structural features of the franchise fee based on the contractual perspective.…”
Section: Introductionsupporting
confidence: 74%
“…Prior researchers have investigated the factors that influence franchise fees mostly based on agency problems and have suggested that the fee structure is determined to minimize agency problems between franchisors and franchisees and induce the best efforts of each party during the contract period (e.g., Brickley 2002;Lafontaine and Shaw 1999;Maruyama and Yamashita 2012;Mathewson and Winter 1985;Roh 2000;Vázquez 2005). Specifically, Zeißler et al (2023) provided empirical evidence that factors to reduce the risk of opportunism (i.e., economic potential, legal right protection, and contract duration) are important for franchise fee decisions in the international franchise setting as well as in the national context, which confirms recent findings on the agency problems (Jayachandran et al 2013;Lanchimba et al 2018). These studies helped us learn the structural features of the franchise fee based on the contractual perspective.…”
Section: Introductionsupporting
confidence: 74%
“…Finally, Zeißler, Mandler, and Kim (2023, “What Drives Royalty Rates in International Franchising?”) address an important gap in the extant literature by using an international EFF approach. They demonstrate that academic studies to date have investigated the “why,” “what,” and “how” criteria of international franchising, but not what drives the key aspect of royalty rates in international franchise agreements.…”
Section: Inaugural Tpgm Special Issuementioning
confidence: 99%